2021
DOI: 10.1214/21-ejs1875
|View full text |Cite
|
Sign up to set email alerts
|

Noncausal counting processes: A queuing perspective

Abstract: We introduce noncausal counting processes, defined by timereversing an INAR(1) process, a non-INAR(1) Markov affine counting process, or a random coefficient INAR(1) [RCINAR(1)] process. The noncausal processes are shown to be generically time irreversible and their calendar time dynamic properties are unreplicable by existing causal models. In particular, they allow for locally bubble-like explosion, while at the same time preserving stationarity. Many of these processes have also closed form calendar time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…4 of Online Appendix 3 for the plot of FED target rate with bubble feature. This process, recently introduced by Gouriéroux and Lu (2021), has the stochastic representation: ytbadbreak=i=1yt+1Zi,tgoodbreak+εt,$$\begin{equation*} y_t=\sum _{i=1}^{y_{t+1}} Z_{i,t}+\epsilon _t, \end{equation*}$$where false(Zi,tfalse)$(Z_{i,t})$ is an i.i.d. sequence of Bernoulli variable with parameter p , and εt$\epsilon _t$ is count‐valued, independent of (Zi,t)i$(Z_{i,t})_i$, with the discrete stable distribution characterized by its LT: double-struckE[evεt]=exp[β(1ev)ν]$\mathbb {E}[e^{v\epsilon _t}]=\exp [-\beta (1-e^v)^\nu ]$.…”
Section: Noncausal Linear Autoregressive Processesmentioning
confidence: 99%
“…4 of Online Appendix 3 for the plot of FED target rate with bubble feature. This process, recently introduced by Gouriéroux and Lu (2021), has the stochastic representation: ytbadbreak=i=1yt+1Zi,tgoodbreak+εt,$$\begin{equation*} y_t=\sum _{i=1}^{y_{t+1}} Z_{i,t}+\epsilon _t, \end{equation*}$$where false(Zi,tfalse)$(Z_{i,t})$ is an i.i.d. sequence of Bernoulli variable with parameter p , and εt$\epsilon _t$ is count‐valued, independent of (Zi,t)i$(Z_{i,t})_i$, with the discrete stable distribution characterized by its LT: double-struckE[evεt]=exp[β(1ev)ν]$\mathbb {E}[e^{v\epsilon _t}]=\exp [-\beta (1-e^v)^\nu ]$.…”
Section: Noncausal Linear Autoregressive Processesmentioning
confidence: 99%
“…(i) From a theoretical point of view, it can be shown that the predictive density l h tends to a discrete distribution with weights p h (ψ) = 1−ψ h at 0 and 1−p h (ψ) at 1/ψ h (see Fries, (2018), for a proof for α-stable AR(1) shocks 8 and Gourieroux and Lu, (2019), proposition 8, for a noncausal count process).…”
Section: Asymptotics Of Cauchy Forecast For Large Y Tmentioning
confidence: 99%